Cimentação de pinos de fibra de vidro: efeito do método de verificação do preparo do conduto e da mistura e inserção de cimento resinoso - Silva, Natércia Rezende da (2017)
Restoration of endodontically treated teeth frequently requires the use of fiberglass post to enable coronary reconstitution, promoting retention to the restoration. The success of the treatment may be influenced by several biological, mechanical and aesthetic factors. This study aimed to evaluate several steps that interfere in the performance of fiberglass post cementation in endodontically treated teeth. This study was divided into four specific objectives; specific objective 1: to evaluate the effect of porosity of self-adhesive resin on the stress distribution, post retention and failure mode of fiber post cemented to human root dentin; specific objective 2: to evaluate the effect of visualization method for post space preparation on root cleanness and on fibre post bond strength. MicroCT and micopushout analysis. Specific objective 3: to evaluate the effect of the resin cement mixing and insertion method into the root canal on resin cement porosity and fiber post push-out bond strength. MicroCT and micopushout analysis. Specific objective 4: to present the clinical protocol of fiberglass post cementation, establishing clinical guidelines for mixing and insertion of self-adhesive resin cements. After analysing the results, it can be concluded that the bubbles generated during resin cement insertion into the root canal negatively affect the stress distribution and the bond strength. The use of confocal microscopy is recommended for failure analysis. The use of magnification devices as loupes and microscopes while performing post space preparation did not improve the bond strength and did not affect in the sealer remain of anterior teeth. Bond strength and porosities is influenced by the mixing process and insertion with endodontic file for luting glass fiber posts. The automix associated to delivery system (endo tip) produced better results for cementing fibreglass posts. The adequate selection of the post system which should only be indicated in the absence of retention for coronary reconstruction and the minimum wear of the tooth structure should be prioritized; the post diameter should be limited to the root canal diameter. Self-adhesive resin cements reduce clinical steps and possible technical errors in glass fiber post cementation and should be mixed and inserted using tips with access to the most apical third of the root canal (centrix for manual mixing cements and endo tips for automix cements). The use of vision magnifying devices such as lupes and surgical microscope are not primordial in the process of clearing the root canal for fiberglass post cementation.